A new species, new genus and new records of heterostigmatic mites (Acari: Heterostigmata) phoretic on scarab beetles of the subfamily Orphninae (Coleoptera: Scarabaeidae) - Khaustov, Alexander A.; Frolov, Andrey V. (Zootaxa, 2018)
During the study of heterostigmatic mites phoretic on beetles of the subfamily Orphninae (Coleoptera: Scarabaeidae), ten species from five families were found. One species, Premicrodispus hajiqanbari sp. nov. (Acari: Microdispidae) phoretic on Orphnus luminosus Benderitter, found in Central African Republic is described as new for science. A new monobasic genus Scarabadania gen. nov. with type species Bakerdania tenuispina Sevastianov, 1974 is created in the family Neopygmephoridae. Troxodania problematica (Mahunka, 1975) comb. nov. (from Bakerdania) and Pseudopygmephorus peritrematus (Mahunka, 1979) (Acari: Neopygmephoridae) are redescribed. Moreover, Trochometridium tribulatum Cross, 1965 (Acari: Trochometridiidae), Troxodania problematica (Mahunka, 1975) comb. nov. and Aegyptophorus shibinensis Sevastianov and Abo-Korah, 1984 (Acari: Neopygmephoridae) are recorded from Sri Lanka for the first time. Finally, Scarabadania tenuispina (Sevastianov, 1974) comb. nov. and Pygmodispus odontotarsus Sevastianov, 1975 (Acari: Scutacaridae) are recorded from Africa for the first time.